PENGARUH FLEKSIBILITAS KEUANGAN, UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Dewi, Putu Ayu Ersa Tresna; Candraningrat, Ica Rika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The desire of investors to invest in certain companies depends on the value of the company which describes the company's performance. This research was carried out because the aim was to analyze the effect of financial flexibility and company size on company value with capital structure as a mediating variable in food and beverage sub-sector companies on the Indonesia Stock Exchange (IDX) in 2019-2021. The increase of 28 samples was determined by purposive sampling. The results of this study indicate that financial flexibility has a positive effect on capital structure and firm value, firm size has no effect on capital structure, firm size has a positive effect on firm value, capital structure has no effect on firm value, and capital structure cannot mediate financial curvature and size company to company value.